Typology of Tactile Architectural Drawings Accessible for Blind and Partially Sighted People - Duniewicz, Agnieszka; Magdziak, Monika (Sustainability, 2022)
The subject of this research is architectural typhlography—tactile drawings, dedicated to the blind and thematically related to architectural objects and spaces of various scales. This collection is very diverse and includes both representations of specific spaces as well as adaptations of ordinary (visually accessible) architectural drawings. The phenomenon of typhlographics has not yet found an appropriate scientific emplacement in the architectural discipline. Based on the collected research material, including Polish and foreign studies, the authors have made a multi-criterial division of the tactile drawings according to specific criteria. The result of the research is a pioneering typology of architectural typhlographs, made in seven categories. This publication, organizing the issues of architectural typhlographs and proposing a unified terminology of the phenomena and concepts studied, may be used by other researchers who explore the subject of the accessibility of architectural space for the blind.